Cardiac recovery from pressure overload is not altered by thyroid hormone status in old mice - Kerp, Helena; Gassen, Janina; Grund, Susanne Camilla; Hönes, Georg Sebastian; Dörr, Stefanie; Mittag, Jens; Härting, Nina; Kaiser, Frank; Moeller, Lars Christian; Lorenz, Kristina; Führer, Dagmar (Frontiers in Endocrinology, 2024)
Thyroid hormones (TH) are known to have various effects on the cardiovascular system. However, the impact of TH levels on preexisting cardiac diseases are still unclear. Pressure overload due to arterial hypertension or aortic stenosis and aging are major risk factors for the development of structural and functional abnormalities and subsequent heart failure. Here, we assessed the sensitivity to altered TH levels in aged mice with maladaptive cardiac hypertrophy and cardiac dysfunction induced by transverse aortic constriction (TAC). Mice at the age of 12 months underwent TAC and received T4 or anti-thyroid medication in the drinking water over the course of 4 weeks after induction of left ventricular pressure overload. T4 excess or deprivation in older mice had no or only very little impact on cardiac function (fractional shortening), cardiac remodeling (cardiac wall thickness, heart weight, cardiomyocyte size, apoptosis and interstitial fibrosis) and mortality. This is surprising, because T4 excess or deprivation had significantly changed the outcome after TAC in young 8-week-old mice. Comparing the gene expression of deiodinase (Dio) 2 and 3 and TH receptor alpha (TRα) 1 and the dominant-negative acting isoform TRα2 between young and aged mice revealed, that aged mice exhibited a higher expression of TRα2 and Dio3 while expression of Dio2 was reduced, compared to young mice. These changes in Dio2 and 3 expressions might lead to reduced TH availability in hearts of 12-month-old mice accompanied by reduced TRα action due to higher TRα2. In summary, our study shows that low and high TH availability have little impact on cardiac function and remodeling in older mice with preexisting pressure induced cardiac damage. This observation seems to be the result of an altered expression of deiodinases and TRα isoforms, thus suggesting that even though cardiovascular risk is increasing with age, the response to TH stress may be dampened in certain conditions.